Solvent effect on hydrogen bonded Tyr⋯Asp⋯Arg triads: Enzymatic catalyzed model system. (December 2016) - Yan, Shihai; Yao, Lishan; Kang, Baotao; Lee, Jin Yong
Graphical abstract: Hydrogen bond plays vital role in structural arrangement, material function, and biological activity of certain enzymatic reactions. The generation or broken of a hydrogen bond varies the kinetics or mechanism of an enzyme reaction. Solvent effect on hydrogen bonded Tyr⋯Asp⋯Arg triads are explored from the geometrical, NBO charges, IR spectra, NMR parameters, and energy viewpoints. The detection and characterization of electron transfer isomer offer useful informaion for mechanism study of biology process and bioactivity. Highlights: The electron transfer isomer observed in anionic triads is useful for mechanism study of biology process and bioactivity. The difference between two hydrogen bonds distance is enlarged by solvent dielectric constant. Distinct variation of the IR spectra characterized the electron transfer isomers. The variations of chemical shift and spin-spin coupling constant are more significant upon electron transfer than solvent dielectric constant. The augmentation of solvent dielectric constant stabilizes the system and enhances the difference of isomers. Abstract: The hydrogen bond plays a vital role in structural arrangement, intermediate state stabilization, materials function, and biological activity of certain enzymatic reactions. The solvent and electronic effects on hydrogen bonds are illustrated employing the polarizable contimuum model at B3LYP/6–311++G(d, p) level. Geometry optimizations reflect the significant solvent and electronic effect. The proton departs spontaneously upon oxidation from the hydroxyl group of tyrosyl in hydrogen bonded Tyr⋯Asp⋯Arg triads in both gas phase and solvents. The electron transfer isomers are observed for anionic triads, no matter what the solvent is. The difference of distance between two hydrogen bonds is enlarged in solvent as compared to that in gas phase. The electronic effect on IR spectra is distinctive. The tyrosyl fragment tends to be oxidized and the arginine moiety is easier to bind an excess electron. The variations of chemical shift and spin-spin coupling constant are more significant upon electron transfer than upon solvent dielectric constant. The augmentation of solvent dielectric constant stabilizes the system, enhances the difference of isomers, and increases the vertical ionization potential and vertical electron affinity values.